Μελέτη όξινης και θερμικής προεπεξεργασίας λιγνοκυτταρινούχας βιομάζας για την παραγωγή βιοκαυσίμων - Δρακόπουλος, Κωνσταντίνος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών. Τομέας Σύνθεσης και Ανάπτυξης Βιομηχανικών Διαδικασιών (IV), 2016)
The continuing pollution of the environment from conventional fuels, but also the unavoidable depletion of their reserves are escalating problems, the solution to which appears to lie on biofuels. In particular, second generation biofuels which exploit raw materials, which are not used for other practical purposes, are suitable as replacements for fossil fuels. In this thesis, an experimental study of biofuels production stages from lignocellulosic biomass, in this case willow wood, was conducted. The part of the process that was studied is that of the pre- treatment, which, due to high costs, is the biggest obstacle in this biofuel production method. The purpose of the pretreatment is to change the structure of the lignocellulosic materials, through saccharification and lignin dissolution, so that the sugars contained in the material could become more accessible for biofuel production. The method chosen was acid and heat pretreatment, in order to find the best combination of temperature and time for optimal results. Willow was processed with dilute acid (HCl 0.1% w/v) at specified times and temperatures. Measurements of the percentage of biomass hydrolyzed, dissolved COD, phenolics, and sugar concentrations were made. From these measurements, it became possible to draw a conclusion about the best pair of temperature and time for the thermal hydrolysis pretreatment. Additionally, a model predicting concentrations as a function of time at different temperatures was constructed. The software used was Aquasim, The model predicts concentrations of dCOD, phenol and sugar concentration versus time for different temperatures.